2016
DOI: 10.4236/ojped.2016.61012
|View full text |Cite
|
Sign up to set email alerts
|

Viral Monitoring and Prevalence of Viral Failure in HIV-1 Infected Children under First Line Antiretroviral Therapy during the First 60 Months of Treatment in Yaoundé, Cameroon: A Serial Cross Sectional Analysis

Abstract: Objective: The objective was to measure the prevalence of viral failure (VF) in HIV-1-infected children on first-line antiretroviral therapy (ART) in routine practice. Methods: Serial cross sectional analysis of viral load (VL) in HIV-1 infected children on first-line ART for ≥24 weeks was done. VL was measured by Real-Time-Polymerase chain reaction (biocentrics). Samples were collected at 6, 12, 24, 36, 48, 60 months of treatment. Main measurement: Virological failure (VF) defined by a one-off VL > 1000 copie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
2
4
2
Order By: Relevance
“…Unlike to our result, higher virological failure was reported from Kenya 23.7% [ 45 ] and 24.6% [ 46 ], Liberia 47% [ 29 ], Zimbabwe 30.6% [ 47 ], Tanzania 57.1% [ 30 ], 32% [ 48 ], Cameroon 20.6% [ 49 ], Ghana 16.7% [ 50 ], Togo 51.6% [ 51 ], Colombia 20.9% [ 18 ], India 69.6% [ 38 ] and Peru 24% [ 52 ]. This difference may be due to lower treatment adherence compared with our study [ 48 , 52 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike to our result, higher virological failure was reported from Kenya 23.7% [ 45 ] and 24.6% [ 46 ], Liberia 47% [ 29 ], Zimbabwe 30.6% [ 47 ], Tanzania 57.1% [ 30 ], 32% [ 48 ], Cameroon 20.6% [ 49 ], Ghana 16.7% [ 50 ], Togo 51.6% [ 51 ], Colombia 20.9% [ 18 ], India 69.6% [ 38 ] and Peru 24% [ 52 ]. This difference may be due to lower treatment adherence compared with our study [ 48 , 52 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with previous studies [32,[35][36][37][38][39][40][41][42], the current study found baseline non-working functional status, low CD4 cell count, advanced WHO clinical stage, and presence of opportunistic infections leads to ART virological failure. Despite this fact, these risk factors are highly interconnected, CD4 cell count is the backbone of immunity construction that helps the human body to protect from the disease and can prevent HIV replication [44].…”
Section: Discussionsupporting
confidence: 92%
“…This finding was comparable with studies conducted in Uganda 11% [26], and it was also in line with studies done in Ethiopia; Tigray (11.5%) [35], Gondar (11.8%) [32] and Bahir Dar Feleg Hiwot (10.7%) [30]. However, the result of the current study, higher virological failure was reported studies done in Kenya 23.7% [22] and Cameron (23.2%) [23], 20.6% [37] and Swaziland 16% [28].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations